Indonesia Government Sets Back: The Rule Of Law, Collaborative Governance And Human Right Challenges During Covid-19 - Warsono, Hardi; Amaliyah, Anita; Putranti, Ika Riswanti; Iannone, Aniello (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
The COVID-19 pandemic has taken mankind by surprise and has caused many governments to impose various rules and strategies to contain it. This article discusses the social impact of government policies during COVID-19, the role of agencies other than the government, and the importance of human rights. Collaborative Governance regime and theory are used to complement qualitative methods and for quantitative method, data collection techniques based on literature research, institutional reports, survey results from journals, online media, and print media, as well as the input of experts in focus group discussions. We found that 1) inconsistencies in policy; 2) lack of coordination and leadership; 3) trust issues; and (4) inequalities and injustice performances increased the pressure on social compliance. Our results indicate that the government needs to be more agile to accommodate, nurture and integrate social actors as governance partners in order to ensure its efficacy, resilience and compliance during this pandemic. The government needs to ensure that an inclusive approach is adopted in multi-dimensional channels so none is left behind and the collaborative governance framework in this pandemic war needs to be improved and implemented. In addition,the government should ensure equal treatment of human rights as specially in human safety in health and safety measures.